2021
DOI: 10.1186/s12984-021-00975-4
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Parkinson’s disease with freezing of gait based on 360° turning analysis using 36 kinematic features

Abstract: Background Freezing of gait (FOG) is a sensitive problem, which is caused by motor control deficits and requires greater attention during postural transitions such as turning in people with Parkinson’s disease (PD). However, the turning characteristics have not yet been extensively investigated to distinguish between people with PD with and without FOG (freezers and non-freezers) based on full-body kinematic analysis during the turning task. The objectives of this study were to identify the mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Meanwhile, the pre-built model of the human body is constructed maturely to fit the extracted related marker positions. Nowadays, Mocap systems have become the golden standard in clinical gait analysis owing to the high tracking accuracy and sampling frequency (Moore et al, 2007 ; Zhang et al, 2018 ; Park et al, 2021 ). However, such systems consisting of multiple pre-deployed cameras are expensive and cumbersome, limiting the applications to hospitals and labs.…”
Section: Gait Analysis Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the pre-built model of the human body is constructed maturely to fit the extracted related marker positions. Nowadays, Mocap systems have become the golden standard in clinical gait analysis owing to the high tracking accuracy and sampling frequency (Moore et al, 2007 ; Zhang et al, 2018 ; Park et al, 2021 ). However, such systems consisting of multiple pre-deployed cameras are expensive and cumbersome, limiting the applications to hospitals and labs.…”
Section: Gait Analysis Methodologymentioning
confidence: 99%
“…For vision-based systems, Guayacán and Mart́ınez ( 2021 ) recently proposed a 3D CNN model that took the spatiotemporal saliency maps of RGB images as input, which achieved 94.1% accuracy (11 PD and 11 HC) under the LOSO validation. In Park et al ( 2021 ), 98.1% detection rate (77 PD and 34 HC) was achieved by using the high precision spatiotemporal and kinematic gait parameters collected by the Mocap system. It can be seen that marker-based systems can provide superior performance in PD detection due the high precision in human skeleton capture, while markerless systems can be deployed in free-living environments.…”
Section: Toward Automatic Recognition In Pd Based On Gait Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this complexity comes with a higher demand on postural control. This has been demonstrated, particularly in patients with Parkinson’s disease [22, 23]. For this reason, it is very important to carefully analyze the turning phases in TUG tests.…”
Section: Introductionmentioning
confidence: 99%
“…Freezers have higher cadence, increased step time variability, and disordered bilateral coordination during turning, deficits that correlate with a greater number of FOG episodes [13,14]. Furthermore, Park et al [15] identified the association between turning characteristics and NFOGQ scores including clinical characteristics demonstrating that increased disease severity in freezers was associated with motor deficits such as stepping inhibition and loss of automaticity during repeated weight locomotion during turning. In addition, provoking FOG or gait instability may occur more frequently during the "end" stage, which is the fourth turning quadrant of the 180 • turning task [10,16].…”
Section: Introductionmentioning
confidence: 99%